Implementation Location-Based Service (LBS) on Mobile Application for Searching Dormitory - Moh Hasan Basri; April Lia Hananto; Siti Masruroh (Information System; Universitas Buana Perjuangan Karawang, 2021)
Abstract—The growth of mobile features, especiallySmartphones at this time can be said to be very developed.Judging from the increasing number of mobile users, theavailability of various mobile features is also growing veryrapidly. In line with these facts, the author aims to create amobile boarding application using Location-Based Service(LBS) technology with the application of the Haversinemethod, making it easier for users to find the closest Dormitory to their place of work with appropriate facilities. Thisapplication is not only to search for Dormitory, it canalso place orders online, this is also an opportunity for themanager or owner of the boarding house to promote their Dormitory. Methods of data collection are done by observation, interviews, literature studies, and documentation. The development of this application system uses the Waterfall method. The final result of this research will create an android-based boarding mobile application that can make it easier for boarding house seekers to search and book boarding houses as well as a means of promotion for boarding house owners and managers.